2016
DOI: 10.1007/s11064-016-2106-7
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Fuels in Epilepsy and Amyotrophic Lateral Sclerosis

Abstract: This review summarises the recent findings on metabolic treatments for epilepsy and Amyotrophic Lateral Sclerosis (ALS) in honour of Professor Ursula Sonnewald. The metabolic impairments in rodent models of these disorders as well as affected patients are being discussed. In both epilepsy and ALS, there are defects in glucose uptake and reduced tricarboxylic acid (TCA) cycling, at least in part due to reduced amounts of C4 TCA cycle intermediates. In addition there are impairments in glycolysis in ALS. A reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 114 publications
0
24
0
2
Order By: Relevance
“…Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disorder characterized by the degeneration of motor neurons in the spinal cord and brain which leads to progressive motor weakness and ultimately death 2 to 5 years from symptom onset due to respiratory failure [115]. Posited mechanisms of motor neuron degeneration include glutamate excitotoxicity, abnormal protein aggregation, impaired axonal transport, inflammation, oxidative stress, and abnormalities in energy metabolism [116]. Altered glucose uptake has been observed in the brain and spinal cord of ALS patients as well as disturbances in energy metabolism [117][118][119][120].…”
Section: Motor Neuron Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disorder characterized by the degeneration of motor neurons in the spinal cord and brain which leads to progressive motor weakness and ultimately death 2 to 5 years from symptom onset due to respiratory failure [115]. Posited mechanisms of motor neuron degeneration include glutamate excitotoxicity, abnormal protein aggregation, impaired axonal transport, inflammation, oxidative stress, and abnormalities in energy metabolism [116]. Altered glucose uptake has been observed in the brain and spinal cord of ALS patients as well as disturbances in energy metabolism [117][118][119][120].…”
Section: Motor Neuron Diseasementioning
confidence: 99%
“…Approaches targeting the metabolic impairments found in ALS through the use of alternative fuels include the Deanna Protocol (a collection of arginine α-ketoglutarate, medium-chain triglycerides, vitamins, and antioxidants), specific medium-chain triglycerides (trioctanoin and triheptanoin) (Fig. 1), and pyruvate dehydrogenase kinase inhibitors [116,121]. Although these have yet to be studied clinically for ALS, preclinical work in rodent ALS models suggests that these approaches improve mitochondrial metabolism, reduce motor neuron toxicity, improve or delay motor symptoms/disease progression, and in some cases extend survival [122][123][124][125][126].…”
Section: Motor Neuron Diseasementioning
confidence: 99%
“…La survie des souris SOD1G93A est ainsi augmentée par l'administration d'inhibiteurs de la PDK1 : ils permettent l'activation de la PDH (pyruvate déshydrogénase sous-unité alpha), stimulent la phosphorylation oxydative et inhibent la glycolyse aérobie [10]. Ainsi, le DCA (dichloro-acétate), un inhibiteur spécifique de la PDK, permet la réactivation de la phosphorylation oxydative, améliorant l'entrée de pyruvate dans le cycle des TCA, maintenant ainsi le métabolisme mitochondrial astrocytaire dans les modèles de souris SOD1G93A [47].…”
Section: Enzymes Glycolytiquesunclassified
“…La réduction de l'activité du cycle des TCA neuronal est associée à une diminution de la glycolyse dans les modèles de SLA [47] avec, notamment, une nette diminution de la phosphorylation oxydative cellulaire et une forte baisse de la production d'ATP [48]. Les concentrations de lactate cytoplasmique sont en effet plus élevées dans les cellules SOD1G93A par rapport à celles mesurées dans les cellules wtSOD1 1).…”
Section: Sla Et Glycolyse Aérobieunclassified
“…Notably, it has recently been shown that feeding triheptanoin, the triglyceride of heptanoate, is a promising dietary intervention that provides an alternative fuel for improving oxidative phosphorylation and increase ATP production in SOD1 mice [22]. Additional suggestions for dietary intervention aimed at restoring metabolic dysfunction by providing alternate fuels have been recently reviewed [23]. Although no dietary intervention has been reported to date in Drosophila models of ALS, hypermetabolism has also been observed in the context of TDP-43 overexpression in motor neurons, which led to a significant increase in pyruvate, the key metabolite linking glucose metabolism to the TCA cycle [24].…”
Section: Systemic Metabolic Alterations In Alsmentioning
confidence: 99%